Research on the control strategy of multi-port DC/DC energy router for the energy Internet - Wenzhong MA; Guancheng LI; Kuitong ZHANG; Shujuan YANG; Mengdi WEI; Yuzhen TANG; Yucheng SONG; Lei DONG (物联网学报)
The characteristics and shortcomings of the current multi-port direct current (DC) to DC (DC/DC) energy router were analyzed.A multi-port DC/DC energy router for the energy Internet was optimized and designed.Through the analysis of the operating voltage requirements under different working conditions,the full-bridge proportional design of the sub-module was proposed.On this basis,an alternating current (AC) to DC (AC/DC) decoupling control strategy to realize riding through the DC fault without de-blocking any devices was proposed.The multi-port DC/DC energy router was used to realize the interconnection of multiple DC power grids with different voltage levels.It not only retained the advantages of low cost and low loss of the traditional DC autotransformer,but also effectively improved the shortcomings that the DC autotransformer cannot ride through the DC fault.Finally,the simulation test was carried out in the MATLAB/Simulink environment to verify the stability of the technology in the normal operation,the feasibility of suppressing the DC fault and the effectiveness of the control strategy.